ENVIRONMENTAL AWARENESS IN EARLY GRADES - SHARMA, KAVITA (THE PRIMARY TEACHER, 2013)
Environmental awareness and understanding, sensitisation towards the related issues and concerns to take appropriate action by all citizens for their addressal has emerged as an important concern of the new millennium. The United Nations (UN) has launched a Decade of Education for Sustainable Development (DESD) since 2005 ‘emphasising that education is an indispensable element for achieving sustainable development’. A curriculum based on the principles of learning of, for and through the environment can play a major role towards accomplishment of the objectives of Education for Sustainable Development (ESD). In India, efforts at the national level reflect the commitment to address this issue as envisaged in the National Policy on Education (NPE) 1986, (modified in 1992) wherein it is clearly mentioned Environmental Awareness in Early Grades Kavita Sharma* that ‘protection of the Environment’ is a common core around which National Curriculum Framework (NCF) would be woven. This concern has been taken care of by all the National Curriculum Frameworks for School Education developed subsequent to the NPE and even prior to this by the National Curriculum Committee, in 1975 policy document.